Efficacy of mindfulness meditation for smoking cessation: A systematic review and meta-analysis. (June 2017) - Maglione, Margaret A.; Maher, Alicia Ruelaz; Ewing, Brett; Colaiaco, Benjamin; Newberry, Sydne; Kandrack, Ryan; Shanman, Roberta M.; Sorbero, Melony E.; Hempel, Susanne
Abstract: Background: Smokers increasingly seek alternative interventions to assist in cessation or reduction efforts. Mindfulness meditation, which facilitates detached observation and paying attention to the present moment with openness, curiosity, and acceptance, has recently been studied as a smoking cessation intervention. Aims: This review synthesizes randomized controlled trials (RCTs) of mindfulness meditation (MM) interventions for smoking cessation. Methods: Five electronic databases were searched from inception to October 2016 to identify English-language RCTs evaluating the efficacy and safety of MM interventions for smoking cessation, reduction, or a decrease in nicotine cravings. Two independent reviewers screened literature using predetermined eligibility criteria, abstracted study-level information, and assessed the quality of included studies. Meta-analyses used the Hartung-Knapp-Sidik-Jonkman method for random-effects models. The quality of evidence was assessed using the GRADE approach. Findings: Ten RCTs of MM interventions for tobacco use met inclusion criteria. Intervention duration, intensity, and comparison conditions varied considerably. Studies used diverse comparators such as the American Lung Association's Freedom from Smoking (FFS) program, quitline counseling, interactive learning, or treatment as usual (TAU). Only one RCT was rated as good quality and reported power calculations indicating sufficient statistical power. Publication bias was detected. Overall, mindfulness meditation did not have significant effects on abstinence or cigarettes per day, relative to comparator groups. The small number of studies and heterogeneity in interventions, comparators, and outcomes precluded detecting systematic differences between adjunctive and monotherapy interventions. No serious adverse events were reported. Conclusions: MM did not differ significantly from comparator interventions in their effects on tobacco use. Low-quality evidence, variability in study design among the small number of existing studies, and publication bias suggest that additional, high-quality adequately powered RCTs should be conducted. Highlights: This systematic review summarizes randomized controlled trials of mindfulness meditation for smoking cessation. Five databases were searched; ten trials met inclusion criteria. Study quality and intervention characteristics varied considerably; this reflects the preliminary state of research in this area. Overall, mindfulness meditation did not have significant effects on abstinence or cigarettes per day, relative to comparator groups.